Retraction notice to “Research on immersive interaction design based on visual and tactile feature analysis of visually impaired children” [Heliyon 10 (2024) e22996] - Tiejun Zhu; Yujin Yang (Heliyon)
This article has been retracted: please see Elsevier policy on article withdrawal (https://www.elsevier.com/about/policies-and-standards/article-withdrawal).The article has been retracted at the request of the Editor-in-Chief.A post-publication investigation conducted by the Elsevier's Research Integrity & Publishing Ethics team on behalf of the journal could not confirm whether or not appropriate ethical approval was given for the research presented in this publication in line with the journal's policy. As it cannot be established whether the article complies with the journal's policies on ethical approval, the editor has lost confidence in the validity/integrity of the article and decided to retract the article.The authors disagree with retraction and dispute the grounds for it.